“As mulheres são a força do futuro": a (des)construção dos estereótipos femininos deflagrados nos comentários de postagens sobre super-heroínas na fanpage de facebook ei nerd - Domiciano, Ive Marian de Carvalho (2023)
In this research, our main objective is to analyze and understand the process of (de)construction of female stereotypes in discourses triggered in comments on posts on a Facebook Fan Page. We use, as a theoretical framework, the Dialogic Discourse Theory (DDT), when it comes to notions of otherness, responsiveness, riddled with valuation (and, therefore, ideological), within a spatial-temporal context (chronotope), and the Theory of Social Representations (TSR), based on Reference Representations (RR) and Use Representations (UR), a division proposed by Py (2000) that was adopted in this work, thus enabling us to understand how these representations are structured by a certain social group around a specific object of representation - here, the female gender, symbolized by the superheroines She-Hulk, Captain Marvel and Wonder Woman. We also emphasize that, in addition to the two theories that served as the basis for our research, we resorted to the notion of stereotype, according to the conception of Amossy and Pierrot (2010); to feminist theories and female representations in comics and audiovisual productions, according to Delphy (1981), Perrot (2008), Beauvoir (1967), Hehl (2016) and Luyten (2019); to the studies of Bakhtin and the Circle (2003) on speech genres; to Ferreira and Frade (2010), Vilela (2010), Silva (2010), Marcuschi (2015), Araújo (2016) and Remenche and Rohling (2016), regarding the emergence of digital speech genres; and, specifically, regarding the online commentary genre, we follow the propositions defended by Melo (2018), Kozinets (2014), Cunha (2014), Santos (2018), Francelino and Oliveira (2018). We were inspired by Marková (2006) to carry out the analysis of social representations regarding the female gender from a discursive perspective. We selected, in the online comments on posts on the Ei Nerd fan page that deal with the three superheroines, excerpts from discursive chains (which we call here, didactically, Comments Block) and, through categories delimited from the two theories, we identified social representations regarding the female gender and found that the majority of subjects participating in this social group feel uncomfortable with female protagonism, especially when it threatens the reference representations constructed by them regarding canonical male characters. Thus, we found representations that confirmed and validated the superhero stereotype that is part of the reference representation of the majority of subjects who are part of this social group: white, curvy, sensual, strong and empowered but without calling into question masculine strength and power. Any construct that deviates, even minimally, from this already anchored representation is criticized and invalidated. We also attested that the low female participation in the discussions (which proves that these virtual spaces for debate regarding comics and their audiovisual adaptations are still mostly occupied by men) and the fact that the subjects were not receptive to contrary opinions made the possibility of more incisive updates of the discourses in which these stereotypes are triggered unfeasible.